2020
DOI: 10.1080/21681805.2020.1788634
|View full text |Cite
|
Sign up to set email alerts
|

The value of a first MRI and targeted biopsies after several years of active surveillance for low-risk prostate cancer – results from the SAMS trial

Abstract: Jäderling (2020) The value of a first MRI and targeted biopsies after several years of active surveillance for low-risk prostate cancer-results from the SAMS trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Given the breadth of our study duration, we employed both standardized template TRUS biopsies and targeted MRI/TRUS fusion biopsies. While reclassification rates were not significantly different between the two procedures, there was a trend towards a higher reclassification rate in the fusion biopsy group, which is congruent with the prior efforts that demonstrated increased Gleason grade progression with the more sensitive and specific fusion biopsies [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 82%
“…Given the breadth of our study duration, we employed both standardized template TRUS biopsies and targeted MRI/TRUS fusion biopsies. While reclassification rates were not significantly different between the two procedures, there was a trend towards a higher reclassification rate in the fusion biopsy group, which is congruent with the prior efforts that demonstrated increased Gleason grade progression with the more sensitive and specific fusion biopsies [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 82%
“…PSAd has also emerged as a powerful predictor of the future behaviour of disease. Studies have shown that in AS, it is a useful predictor of biopsy upgrading, aids MRI in predicting early reclassification, and informs repeat biopsy interval [35] , [36] , [37] . Remarkably, both our work and others’ works have demonstrated the key threshold of PSAd of ≥0.15 in differentiating future behaviour [11] , [38] , [39] .…”
Section: Discussionmentioning
confidence: 99%